ESL Students feedback on the use of blogs for language learning - Nadrah Abu Bakar,; Hafizah Latif,; Azizah Ya’acob, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2010)
The proliferation of the information and communication technology has provided university educators and e-learning practitioners with the technological tools that can be implemented as pedagogical instruments in the classrooms. This paper provides an account of how the blog was integrated as a pedagogical tool in the ESL classrooms and reports on the students’ feedback and perception on the use of this social medium to enhance their L2 learning. Data was collected via a survey questionnaire involving a selected cohort of low proficiency ESL students at tertiary level. Using the proposed framework, the students carried out several stages of the blogging activities embedded in the English for Social Sciences Course that they were taking at the end of which the questionnaire was administered. Analysis of data in the main indicated positive responses from the students regarding the use of blogs in L2 their learning activities. They perceived that the use of blog had generally enhanced their L2 skills such as reading and writing,developed their self-confidence, improved their communication skills and reduced their anxiety when learning and using the language among their peers. The paper ends by highlighting the benefits that can be gained as a result of the implementation of the weblog in language learning classrooms.